Do characteristics of pollinator‐friendly gardens predict the diversity, abundance, and reproduction of butterflies?. Issue 4 (17th January 2018) - Majewska, Ania A.; Sims, Stuart; Wenger, Seth J.; Davis, Andrew K.; Altizer, Sonia
Abstract: Pollinator declines have motivated efforts to plant nectar and host plants for butterflies and other pollinators, but whether gardens promote pollinator conservation requires further investigation. We established garden plots to determine whether plant type (native vs. exotic) and weed maintenance (low or high) influence adult butterfly abundance and species richness, and the abundance and survival of immature stages of four species (monarch, queen, black swallowtail, and gulf fritillary). To assess how predator activity and mortality of immature stages might differ inside gardens compared to other suitable habitat patches, we compared caterpillar survival on sentinel host plants placed within and outside of plots. The abundance and species richness of adult butterflies (all taxa) increased with the number of flowering plants per plot, but did not depend on plant type or weeding treatment. Exotic plots had greater adult monarch and gulf fritillary abundances, greater monarch and queen egg counts, and lower black swallowtail caterpillar counts relative to native plots. The survival of immature stages (egg to instar 5) ranged from 2 to 13% and was similar across plots, except for gulf fritillary larvae, which had higher survival in exotic plots. Monarch caterpillar mortality risk was higher on sentinel plants placed inside plots, relative to those outside of plots. This study suggests that garden plots attracted a diversity of adult butterflies and supported the reproduction of focal species. Given lower immature monarch survival within versus outside of plots, further work is needed to examine natural enemy pressure within pollinator gardens.